Enhancing Student Well-being: Child-Friendly School Management in Conflict-Affected Areas - Aisyah, Eny Nur (JURNAL AL-TANZIM, 2024)
The relevance of this study lies in the urgent need to provide a safe, inclusive, and supportive educational environment for children in areas affected by social and ethnic conflict. This study highlights inclusive policies, psychosocial support, and community engagement in creating a supportive learning environment. This study used a qualitative method with a case study approach involving in-depth interviews, participant observation, and document analysis as data collection techniques. Data were collected through in-depth interviews, participant observation, and document analysis. The results showed that inclusive policies, psychosocial support through counselling and extracurricular activities, and teacher training in inclusive teaching methods effectively created a safe and supportive learning environment for students. In addition, empowering local communities and cultivating positive behaviours were essential in supporting student well-being. The implications of this study suggest that a holistic approach to school management can improve the quality of education and the well-being of children in conflict-prone areas and provide practical recommendations for other schools facing similar situations.